2018
DOI: 10.1080/19932820.2018.1512330
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of bone and cartilage biomarkers: correlation with structural damage in rheumatoid arthritis

Abstract: The aim of our study was to assess the relationship between bone and cartilage remodeling biomarkers and joint damage in Rheumatoid Arthritis (RA), and to detect whether they have the capacity to predict the progression of joint disease assessment by computed tomography (CT) erosion score. We analyzed 65 female patients with established RA in our Rheumatology Department. Serum levels of bone and cartilage markers were measured: osteocalcin (OC), N-propeptide of type I collagen (PINP), collagen type I and II, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Both I-CTX and PINP are key biomarkers of bone remodeling. 10 In addition, many studies have focused on the association between IL-6 and BMD, and advocated IL-6 play an important role in affecting normal bone metabolism and leading to osteoporosis. 11 In Sun’s study, the level of IL-6 was found to be negatively correlated to BMD, and indicating chronic inflammation may increase the serum RANKLE, leading to the occurrence of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both I-CTX and PINP are key biomarkers of bone remodeling. 10 In addition, many studies have focused on the association between IL-6 and BMD, and advocated IL-6 play an important role in affecting normal bone metabolism and leading to osteoporosis. 11 In Sun’s study, the level of IL-6 was found to be negatively correlated to BMD, and indicating chronic inflammation may increase the serum RANKLE, leading to the occurrence of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…RA is a chronic systemic connective tissue disease with a worldwide prevalence of 1 to 1.5%. 2,3 Women are three times more frequently affected than men. The hallmark features of RA are synovitis, tenosynovitis, and subchondral bone marrow inflammation that can lead to bone erosions, cartilage damage, and tendon tears.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Furthermore, serum COMP level correlated to disease activity of RA [104] and had superior sensitivity, specificity, and accuracy for diagnosis of RA [105]. Serum collagen type I (TXI) was also associated with RA disease activity [106]. Serum levels of C1M (a product of MMP-cleavage of type I collagen) and C3M (MMP-9-mediated type III collagen degradation product) were able to discriminate between the undifferentiated arthritis and RA diagnosis [107].…”
Section: Utility Of Chondrocyte Products As Diagnostic and Prognosticmentioning
confidence: 99%